TREND IN MATERNAL MORTALITY IN NORTH ACEH REGENCY FOR A DECADE: INFLUENCE OF SOCIO-CULTURAL FACTORS - Maidar, Maidar; Zakaria, Radhiah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: The Global Millennium Development Goals (MDGs) commitment targets reducing the Maternal Mortality Rate (MMR) to 102 per 100,000 live births by 2015, followe by the Sustainable Development Goals (SDGs) setting a new target of 70 per 100,000 live births in 2030. For a decade or ten years of observations of maternal mortality trends in North Aceh Regency still show fluctuations. Method: This study examines the relationship between socio-cultural factors and cases of maternal death. Qualitative research by conducting (1) in-depth interviews with 10 key informants, namely midwives who provide services; (2) Focus Group Discussion with Puskesmas Management and Program Responsible Persons on maternal death case audit activities; (3) Documentation study of the track record of maternal deaths in the decade period 2013-2022. Result: The results shows that there is a downward trend although fluctuations of increase and decrease still occur within a decade of observation. The main immediate causes are due to bleeding and hypertension in pregnancy, the predominant place of death is in the hospital. The characteristics of multiparity mothers, ‘4 too’ pregnancies and delays in recognizing problems and making decisions indicate that socio-cultural factors are very influential on maternal mortality in North Aceh. Recommendation: Innovation is needed to reconstruct socio-cultural disadvantages such as late decisions making and the ideal number of children in a family.